KONSERVASI ENERGI LISTRIK PADA BANGUNAN GEDUNG KANTOR BUPATI TOJO UNA-UNA - Jordan A. Tiro; Baso Mukhlis; Agustinus Kali; Irwan Mahmudi (Foristek, 2021)
Electrical energy has a very important role in the economic, industrial and social development of the community, this causes an increase in the demand for electrical energy in line with the increase in people's welfare, economic and industrial growth. On the other side, energy sources that are commonly used for power generation are increasingly expensive and limited in availability and cause environmental pollution. Based on these considerations, it is necessary to implement an energy management program to preserve energy resources and use energy effectively. Energy consumption intensity (ECI) is a term used to determine the amount of electrical energy consumption in a room. The calculation of the intensity of energy consumption carried out at the Tojo Una-una regent's office in Central Sulawesi consists of 3 buildings with 129 rooms, it was found that 7 rooms were categorized as quite efficient and wasteful.